2021
DOI: 10.3390/insects12100952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypoxia on the Lethal Mortality Time of Adult Sitophilus oryzae L.

Abstract: Sitophilus oryzae is one of the most destructive pests of stored grains. It leads to significant quantitative and qualitative losses, resulting in food and income insecurity among farmers. Chemical pesticides are the most common methods used by farmers and other grain value chain actors to manage this pest. However, pesticides are increasingly becoming unattractive for pest control due to health hazards posed to applicators, consumers, the environment, and insect resistance. Modified atmospheres have the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…No adults emerged within 50 days post-treatment after insects were exposed to hypoxia from 20 and 30 germinating seeds for 120 and 96 h, respectively. Previous research showed that exposure of insects to low oxygen (e.g., 1%) for a few days resulted in no adult emergence within 45 days post-treatment [22,25]. Similar results were achieved using other gases, such as CO 2 .…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…No adults emerged within 50 days post-treatment after insects were exposed to hypoxia from 20 and 30 germinating seeds for 120 and 96 h, respectively. Previous research showed that exposure of insects to low oxygen (e.g., 1%) for a few days resulted in no adult emergence within 45 days post-treatment [22,25]. Similar results were achieved using other gases, such as CO 2 .…”
Section: Discussionsupporting
confidence: 70%
“…A higher number of germinating seeds led to quicker oxygen depletion and earlier adult mortality. Similar adult mortality (within 4 days) was observed when oxygen levels were maintained at 1% using nitrogen [22,36]. Faster oxygen depletion meant that insects experienced prolonged exposure to lower hypoxia, accelerating adult mortality.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…From the perspective of international research and development dynamics, the focus of technological innovation in the coming period is to research and develop automatic control systems for grain storage ventilation and cooling with artificial intelligence [ 67 ]. The main purpose of air conditioning grain storage technology is to kill pests by changing the concentration of O 2 , N 2 , and CO 2 in the air [ 69 ]. Although the cost of fumigation is higher than the general fumigation technology, it can effectively maintain the grain quality without any pollution of the stored grain and does not affect human health [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some insects can survive and propagate under rather dry conditions, till about 30% RH (Roberts 1972), but insects are sensitive to sub-zero temperatures and hypoxia. Both conditions are recommended as alternative for chemical fumigation (Kalpana et al 2022;Kandel et al 2021). However, it should be considered that the eggs or pupae can have, related to their low metabolic activity, a greater tolerance compared to the adult insects and modified atmospheric treatments can take some weeks, also depending on the temperature.…”
Section: Pests and Pathogensmentioning
confidence: 99%